Teachers’ Job Satisfaction in Instructional Delivery Modalities, and the Role of School Leaders: A Study among Selected Private Schools in the UAE - Ahmad Yahya; Solomon Arulraj David (International Journal of Educational Administration, Management, and Leadership, 2022)
The purpose of this paper is twofold. Firstly, to analyse the impact of the newly applied instructional delivery modalities on teachers’ job satisfaction. Secondly, to navigate the role of school leaders to help teachers to cope with these models. The teaching modalities that are of research interest are the face-to-face, online, and hybrid models. The study adopted the mixed-methods approach. Around 151 teachers from 3 private schools in Abu Dhabi shared their response in a quantitative survey. To compare the teachers’ job satisfaction, the following mediating variables were considered: job security, workload, in-class effort, work-life balance, remuneration, leadership support, students’ behaviour, and relationship with co-workers. On the other hand, semi-structured interviews with 20 staff from the 3 schools were conducted to explore the best practices that school leaders can apply to meet the teachers’ job satisfaction. The findings of the study confirmed that there is a significant association between teaching modality and teachers’ job satisfaction. The traditional teaching modality meets the highest level of satisfaction, then the distance learning, and lastly is the hybrid one. Whereas the interviews recommended that school leaders are asked to build active communication channels with their teachers, share the decision-making process, decrease the workload, raise the teachers’ autonomy, and establish a remuneration system. The study concludes that teachers’ job satisfaction in all instructional delivery models should be a priority for every successful school leader.